2014
DOI: 10.1111/imj.12489
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of upper gastrointestinal haemorrhage in Maori and New Zealand European ethnic groups, 2001–2010

Abstract: AAI of UGIH in the Waikato region was 46.4. This was significantly higher in Maori and in males, and decreased over the study period. These data will provide a comparison for future assessment of trends in UGIH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…Compared with the present study, the incidence rates of upper GIB in the United States (from 1998 to 2006) were higher at between 1.46 and 1.70 per 1000 person-years and were comparable to those of Spain (from 1996 to 2005), which ranged from 0.47 to 0.87 per 1000 person-years . Furthermore, similar to the present study, these studies showed decreased or stable incidence of upper GIB over the years, a higher incidence in men than in women, and increased incidence with age . Few studies that reported the incidence of lower GIB in the general population showed that the rates in the United States (1998-2006), Spain (1996-2005), and Italy (2001-2010) were about half of the rate reported in our study .…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Compared with the present study, the incidence rates of upper GIB in the United States (from 1998 to 2006) were higher at between 1.46 and 1.70 per 1000 person-years and were comparable to those of Spain (from 1996 to 2005), which ranged from 0.47 to 0.87 per 1000 person-years . Furthermore, similar to the present study, these studies showed decreased or stable incidence of upper GIB over the years, a higher incidence in men than in women, and increased incidence with age . Few studies that reported the incidence of lower GIB in the general population showed that the rates in the United States (1998-2006), Spain (1996-2005), and Italy (2001-2010) were about half of the rate reported in our study .…”
Section: Discussionsupporting
confidence: 68%
“…Downloaded From: https://jamanetwork.com/ on 10/31/2020 incidence with age. 2,[11][12][13]25,26 Few studies that reported the incidence of lower GIB in the general population showed that the rates in the United States (1998States ( -2006, Spain (1996Spain ( -2005, and Italy (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010) were about half of the rate reported in our study. [10][11][12] Similar to this study, previous studies [10][11][12] reported a slight increasing trend in the incidence of lower GIB or complications.…”
Section: Discussionmentioning
confidence: 75%
“…Our ndings are largely consistent with those of other New Zealand (13)(14)(15) and international (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) studies that have also found higher rates of major bleeds (total, gastrointestinal or intracranial) in non-Whites compared with Whites and with increasing socioeconomic deprivation. In these studies, populations were not de ned according to their history of CVD and AF, and there was adjustment for a limited number of variables, if any.…”
Section: Discussionsupporting
confidence: 90%
“…3,24,[36][37][38][39] The variability in incidence rates is mainly caused by the variance of methodology used in diagnosing UGIB. However, despite this limitation, the information corroborates decreasing incidence of UGIB all over the world.…”
Section: Worldwide/regional Incidencementioning
confidence: 99%